Haptic Teaching-Learning Practices in Architecture Education (Journal of Advanced Research in Civil Engineering and Architecture, 2020)
In any teaching-learning setting, understanding the applicability of concepts becomes ambiguous if they are communicated only through verbal and visual methods. In this context, architecture, being the most powerful visible expression of human spirit, is no exception. Research by cognitive scientists places high emphasis on the fact that physical connection of students to their work results in improved teaching-learning processes to get them involved in the work and further prepares them well to make informed decisions while dealing with professional challenges. Hence, haptic (kinaesthetic sensitivity) way of teaching-learning practices is the most appropriate methodology as it combines verbal and visual matter to help in concretising concepts in real time. Against this backdrop, the paper discusses various significant haptic teaching-learning processes and techniques that can be developed to support student's ability to formulate better methodologies to propose pragmatic design solutions that respond positively to context, temporal and the ever-advancing construction technology. Further, this paper discusses the positive implications and integration of haptic practices in the curricula through a workshop cum competition held for the undergraduate students of architecture.